STUDI KESENJANGAN ANTARA TINGKAT KEPUASAN PELANGGAN DENGAN TINGKAT KEPENTINGAN LAYANAN PADA BLITZ MEGAPLEX DI JAKARTA - Grace Hartanti; Asnan Furinto (Bina Nusantara University, 2009)
The pursuit of customer satisfaction toward service quality is a simple and yet inevitable effort for companies in the service industry. Customer satisfaction is expected to impact customer loyalty which materializes as among others, the spread of word of mouth, creating more customers and bringing more profits for the company. The common problem in the area of customer satisfaction and service quality measurement is the existence of gap between what the customers expect to receive and what the company eventually delivers to them. Another possible gap is on the types of service attributes. Those attributes which are deemed important or unimportant by customers are sometimes (if not most of the time) different from what company perceives to be important or unimportant. To complicate the picture further, there are also difference of perspectives between member and non member customers. Blitz Megaplex is a service company, providing one stop entertainment-beyond movies, to their customers. This research aims to provide insights to Blitz management as to on what dimensions of service quality they shall put more emphasize on. Using combination of explorative and quantitative approach to collect data, the author further employs IPA (Importance-Performance Analysis) framework to analyze the findings. It is found that there are significant gaps at the three locations of Blitz Megaplex (Grand Indonesia, Pacific Place, Mal of Indonesia) in Jakarta. Blitz shall focus on important dimensions (as rated by customers) whereby its performance is falling below customer expectation, and shall reduce its efforts of improving unimportant dimensions even though it is performing way above customer expectation.